Predicate of "Mangan" in Sasak Language: A Study of Natural Semantic Metalanguage - Sarwadi, Sarwadi (Lingual Journal of Language and Culture, 2016)
The aim of this study were to know semantic meaning of predicate Ngajengan, Daharan, Ngelor, Mangan, Ngrodok (Eating), Kaken (Eating), Suap, Bejijit, (Eating) Bekeruak (Eating), Ngerasak (Eating) and Nyangklok (Eating). Besides that, to know the lexical meaning of each words and the function of words in every sentences especially the meaning of eating in Sasaknese language. The lexical meaning of Ngajengan, Daharan, Ngelor, Mangan, Ngrodok (Eating), Kaken (Eating), Suap, Bejijit, (Eating) Bekeruak (Eating), Ngerasak (Eating) and Nyangklok (Eating) was doing something to eat but the differences of these words are usage in sentences. Besides that, the word usage based on the subject and object and there is predicate that need tool to state eat meals or food.
Keywords: semantic meaning, Sasaknese language.